Conductive silver paste and preparation method and application thereof
By adding glycidyl ether epoxy resin, phenolic epoxy resin and phenoxy resin to the conductive silver paste to form polymer chain segments and particle dispersed phases, the problems of low welding tension and high resistivity of the conductive silver paste are solved. The effect of high welding pull force and low resistivity is achieved.
Patent Information
- Application Number
- CN202310551963.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-05-16
AI Technical Summary
The welding tension of existing conductive silver paste is relatively low and the resistivity is relatively high, which affects the welding stability of photovoltaic modules.
By adding thermosetting glycidyl ether epoxy resin and phenolic epoxy resin to the silver powder, and introducing phenoxy resin as an additive, interpenetrating and continuous polymer chain segments and independent particle dispersed phases are formed to increase the welding tensile strength. and conductive properties.
The high welding pull force and low resistivity of the conductive silver paste are achieved, and the welding stability and conductive performance of the photovoltaic module are enhanced.
Smart Images

Figure BDA0004231787220000081 
Figure BDA0004231787220000082 
Figure BDA0004231787220000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic pastes, and in particular relates to a conductive silver paste and a preparation method and application thereof. Background Art
[0002] Heterojunction cells are a type of solar cell, usually including amorphous silicon thin film, TCO thin film and conductive grid lines. At present, grid lines printed with silver paste have become the mainstream development trend. According to the thickness and application of the grid lines, they can be mainly divided into two categories: main grid and fine grid. Among them, the main grid not only has strict requirements on the conductivity and printability of the silver paste, but also requires it to have a certain welding tension to achieve long-term stable and safe use.
[0003] However, the main problems in the prior art are that the welding tension of the silver paste is relatively low and the resistivity is relatively high. The welding tension problem will seriously affect the welding of photovoltaic modules. An improvement measure that does not affect the conductivity of the silver paste and can increase the welding tension of the silver paste is urgently needed to be developed. Summary of the invention
[0004] The object of the present invention is to overcome the deficiencies of the prior art and provide a conductive silver paste with high welding tension and high conductivity.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a conductive silver paste, comprising the following raw materials in percentage by weight: 80-94% silver powder, 3-6% epoxy resin, 0.1-10% curing agent, 1-5% solvent, and 1-3% additive;
[0007] The epoxy resin includes glycidyl ether epoxy resin and phenolic epoxy resin;
[0008] Additives include phenoxy resins;
[0009] The masses of the phenoxy resin, glycidyl ether epoxy resin and novolac epoxy resin satisfy: S: (a×1.5%+b×6%)=(1-2), wherein: S is the mass of the phenoxy resin, a is the mass of the glycidyl ether epoxy resin, and b is the mass of the novolac epoxy resin.
[0010] The inventors of the present invention have found that the present invention adds thermosetting glycidyl ether epoxy resin and phenolic epoxy resin to silver powder, which can transform the silver powder from a loose powdery morphology to a structure with a specific pattern and close contact with each other. However, after uniform mixing, the glycidyl ether epoxy resin and the phenolic epoxy resin will form mutually penetrating and continuous polymer chain segments, and after curing, they will form a dense and rigid material, which is easy to break due to the impact of external force. The present invention introduces phenoxy resin as an additive to form an independent particle dispersion phase in the above-mentioned chain segment. When external force acts on the entire cured system, it can achieve the effect of stress release and crack termination, thereby improving the welding tensile force of the conductive silver paste.
[0011] In addition, the mass ratio of the phenoxy resin, the glycidyl ether epoxy resin and the phenolic epoxy resin of the present invention meets the above range, which can make the silver powder in the conductive silver paste maintain a more compact structure, and is more conducive to the formation of the dispersed phase of the epoxy resin particles, so that the conductive silver paste has better electrical conductivity and welding tension. When the amount of phenoxy resin added is small, it cannot achieve the effect of releasing stress and terminating cracks, so that the welding tension of the conductive silver paste is low; when the amount of phenoxy resin added is large, the viscosity of the conductive silver paste is too large, which seriously damages the integrity of the grid line after the paste is printed, which is not conducive to the migration of photoelectrons, thereby reducing the conductive performance of the conductive silver paste.
[0012] As a preferred embodiment of the conductive silver paste of the present invention, the weight average molecular weight ratio of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin is glycidyl ether epoxy resin: novolac epoxy resin: phenoxy resin = 1: (1.5-10): (10-100).
[0013] The inventors of the present invention have found that when the weight average molecular weight ratio of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin is within the above range, the shrinkage of the conductive silver paste during the curing process can be effectively reduced, thereby avoiding the generation of micro cracks due to the large shrinkage. When the molecular weight of the phenoxy resin is small, the performance requirement of reducing the shrinkage during the curing process of the conductive silver paste cannot be met, resulting in cracking of the grid line after the conductive silver paste is printed; and when the molecular weight of the phenoxy resin is large, the rheological properties of the paste are poor due to excessive cross-linking of the resin, which is not conducive to the printing of the conductive silver paste.
[0014] As a more preferred embodiment of the conductive silver paste of the present invention, the weight average molecular weight of the glycidyl ether epoxy resin is 100-500, the weight average molecular weight of the phenolic epoxy resin is 150-5000, and the weight average molecular weight of the phenoxy resin is 10000-80000.
[0015] The inventors of the present invention have found that the weight average molecular weight of the glycidyl ether epoxy resin, phenolic epoxy resin and phenoxy resin of the present invention is within the above range, which is more conducive to the formation of a particle dispersed phase of the polymer chain segment, thereby making the conductive silver paste have a higher welding tensile force.
[0016] As a preferred embodiment of the conductive silver paste of the present invention, the epoxy equivalent ratio of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin is glycidyl ether epoxy resin: novolac epoxy resin: phenoxy resin = 1: (1.5-5): (1-10).
[0017] The inventors of the present invention have conducted extensive research on the epoxy equivalents of epoxy resins and phenoxy resins and found that the ratio of the epoxy equivalents of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin of the present invention within the above range is conducive to improving the printability of the paste, making the rigidity and toughness of the grid line in a more suitable range, and also improving its mechanical strength and its adhesion to the substrate, so that the conductive silver paste has a higher welding tensile force. When the epoxy equivalent of the glycidyl ether epoxy resin, the novolac epoxy resin or the phenoxy resin is high, it is not conducive to the formation of a particle dispersed phase by the polymer chain segment, thereby reducing the welding tensile force of the conductive silver paste.
[0018] As a more preferred embodiment of the conductive silver paste of the present invention, the epoxy equivalent of the glycidyl ether epoxy resin is 50 to 300 g / eq, the epoxy equivalent of the phenolic epoxy resin is 100 to 500 g / eq, and the epoxy equivalent of the phenoxy resin is 500 to 5000 g / eq.
[0019] The inventors of the present invention have found that the present invention selects glycidyl ether epoxy resin, novolac epoxy resin and phenoxy resin within the above-mentioned epoxy equivalent range, and by limiting the range of epoxy equivalents of each component, the welding tension after curing of the conductive silver paste can be further guaranteed. However, when the epoxy equivalents of the glycidyl ether epoxy resin, novolac epoxy resin and phenoxy resin do not meet the above-mentioned range, but the epoxy equivalent ratio of the three resins is controlled to be 1: (1.5-5): (1-10), the epoxy equivalent of the resin may be too low, thereby affecting the interaction between the resins and causing the welding tension of the conductive silver paste to decrease.
[0020] As a preferred embodiment of the conductive silver paste of the present invention, in the epoxy resin, the mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin is glycidyl ether epoxy resin:phenolic epoxy resin=(1-4):1.
[0021] The mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin of the present invention is within the above range, which is more conducive to forming a structure in which the silver powder forms a specific pattern and is in close contact with each other, and is conducive to enhancing the migration of photogenerated electrons, so that the conductive silver paste has better conductivity.
[0022] As a more preferred embodiment of the conductive silver paste of the present invention, in the epoxy resin, the mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin is glycidyl ether epoxy resin:phenolic epoxy resin=(1.5-3):1.
[0023] The mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin of the present invention is within the above range, which can optimize the conductive performance of the conductive silver paste.
[0024] As a preferred embodiment of the conductive silver paste of the present invention, the glycidyl ether epoxy resin is selected from bisphenol A epoxy resin and / or bisphenol F epoxy resin, and the novolac epoxy resin is selected from at least one of phenol-type novolac epoxy resin, cresol-type novolac epoxy resin and bisphenol A novolac epoxy resin.
[0025] As a preferred embodiment of the conductive silver paste of the present invention, the silver powder includes flaky silver powder, spherical silver powder A and spherical silver powder B;
[0026] The thickness of the flaky silver powder is 0.5 to 5 μm, the particle size of the flaky silver powder is 6 to 15 μm, and the aspect ratio of the flaky silver powder is 2 to 20; the particle size of the spherical silver powder A is 1 to 5 μm, and the particle size of the spherical silver powder B is 0.1 to 3 μm.
[0027] The inventor of the present invention has found that the present invention uses the above-mentioned specific silver powder and adds specific epoxy resin and phenoxy resin additives, which is more conducive to forming a structure with a specific pattern and close contact with each other. Among them, the flaky silver powder with a specific particle size and thickness can ensure that the surface of the photovoltaic grid line after printing has a certain conductivity and a certain welding tension; the combination of two spherical silver powders with different particle sizes can ensure the close accumulation of silver powder, thereby improving the printability of the slurry and making the grid line surface smoother.
[0028] As a preferred embodiment of the conductive silver paste of the present invention, the particle size of the flaky silver powder is 6.5 to 8 μm.
[0029] The inventors of the present invention have found that the use of the above-mentioned specific silver powder in the present invention is conducive to enhancing the conductivity of the surface of the photovoltaic grid line after printing. If the particle size of the flake powder is smaller than the above-mentioned range, the conductivity of the photovoltaic grid line is insufficient and the welding tension is reduced; if the particle size of the flake powder is larger than the above-mentioned range, the fluidity of the slurry becomes poor.
[0030] As a preferred embodiment of the conductive silver paste of the present invention, based on the total mass of the conductive silver paste, the mass percentage of the flaky silver powder is 30-60%, the mass percentage of the spherical silver powder A is 10-30%, and the mass percentage of the spherical silver powder B is 10-30%.
[0031] The inventors of the present invention have found that the mass percentage of the flaky silver powder, spherical silver powder A and spherical silver powder B in the present invention is within the above range, which is conducive to ensuring the fluidity of the silver paste and the conductivity of the formed grid lines. When the content of the spherical silver powder A or the spherical silver powder B is high, the printability of the paste is better and the grid lines are smoother, but it will lead to increased costs; and when the content of the flaky silver powder is high, although it can make the volume resistivity easier to reduce and the cost is lower, the fluidity of the paste becomes worse, thereby increasing the roughness of the grid lines.
[0032] As a more preferred embodiment of the conductive silver paste of the present invention, based on the total mass of the conductive silver paste, the mass percentage of the flaky silver powder is 45-50%, the mass percentage of the spherical silver powder A is 20-25%, and the mass percentage of the spherical silver powder B is 20-25%.
[0033] The inventors of the present invention have found that when the mass percentages of the flaky silver powder, spherical silver powder A and spherical silver powder B of the present invention are within the above range, the fluidity of the silver paste and the conductivity of the formed grid lines can be further guaranteed. The present invention uses a higher proportion of flaky silver powder, which is more conducive to reducing the resistance and cost of the conductive silver paste; when the proportion of flaky silver powder is too high, it is difficult to form a structure with a specific pattern and in close contact with each other.
[0034] In a second aspect, the present invention further provides a method for preparing the above-mentioned conductive silver paste, comprising the following steps:
[0035] S1, mixing epoxy resin, curing agent, solvent and additives in proportion to obtain a mixture A;
[0036] S2, adding silver powder to the mixed material A in step S1, mixing evenly, to obtain the conductive silver paste.
[0037] As a preferred embodiment of the preparation method of the present invention, in step S2, the mixing method comprises the following steps: firstly stirring and premixing, and then uniformly dispersing through a three-roll mill;
[0038] The stirring speed is 100-800 r / min.
[0039] In a third aspect, the present invention also provides the use of the above-mentioned conductive silver paste in the preparation of heterojunction batteries.
[0040] The conductive silver paste of the present invention can simultaneously have high conductivity and welding tension, which is conducive to solving the problem that the conventional conductive silver paste affects the welding of photovoltaic modules due to low welding tension when preparing heterojunction batteries.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The present invention adds thermosetting glycidyl ether epoxy resin and phenolic epoxy resin to silver powder, which can transform the silver powder from a loose powdery morphology to a structure with a specific pattern and close contact with each other. However, after uniform mixing, the glycidyl ether epoxy resin and the phenolic epoxy resin will form mutually penetrating and continuous polymer chain segments, and after curing, they will form a dense and rigid material that is easily broken due to the impact of external forces. The present invention introduces phenoxy resin as an additive to form an independent particle dispersion phase in the above-mentioned chain segments. When external force acts on the entire cured system, the polymer chain segments can form a particle dispersion phase to achieve the effect of stress release and crack termination, thereby improving the welding tension of the conductive silver paste;
[0043] (2) The mass ratio of the phenoxy resin, the glycidyl ether epoxy resin and the phenolic epoxy resin of the present invention satisfies the above range, which can enable the silver powder in the conductive silver paste to maintain a more compact structure and is more conducive to the formation of a particle dispersed phase of the epoxy resin, thereby enabling the conductive silver paste to have better electrical conductivity and welding tensile force. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The pattern morphology of the conductive paste screen-printed in the effect example of the present invention;
[0045] Figure 2 It is a schematic diagram of wire bonding using conductive paste in an example of the effect of the present invention. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The methods or operations used in the embodiments, unless otherwise specified, are conventional methods or conventional operations in the art.
[0047] The brands of phenoxy resin used in the present invention include but are not limited to any one of YP-50S, PKHW-34, PKHW-35, PKHB, PKHC, PKHH, and PHEA.
[0048] The curing agent used in the present invention is not particularly limited and can be any compound that can cure the epoxy resin of the present invention. The curing agent used in the present invention includes, for example, but is not limited to: (1) polyamine curing agents, such as linear fatty amines (linear fatty amines can be at least one of DETA, TETA, TEPA, and DEPA), alicyclic amines (alicyclic amines can be at least one of MDA, IPDA, N-AEP, and ATU adducts), aromatic amines (aromatic amines can be at least one of m-XDA, DDM, m-PDA, and DDS), and polyamides; (2) anhydride curing agents, such as monofunctional anhydrides (monofunctional anhydrides can be at least one of PA, THPA, HHPA, MeTHPA, MeHHPA, MNA, DDSA, and HET), difunctional anhydrides (difunctional anhydrides Anhydride can be at least one of PMDA, BTDA, TMEG, MCTC), carboxyl anhydride (carboxyl anhydride can be TMA and / or PAPA); (3) polyphenol curing agent, such as PN; (4) polythiol curing agent, such as PM and / or PS; (5) anionic polymer curing agent, such as imidazole compound (imidazole compound can be at least one of 2MZ, 2E4MZ, 2PZ, 2MZ-CN, 2E4MZ-CN, C11Z, C17Z, 2P4MZ); (6) cationic polymer curing agent, such as boron trifluoride amine complex (boron trifluoride amine complex can be at least one of BF3-MEA, BF3-BZA, BF3-DMA).
[0049] The solvent used in the present invention is used to adjust the viscosity and fluidity of the conductive silver paste. The type of solvent is not particularly limited and can be any solvent known to those with ordinary knowledge in the technical field of the present invention. The solvent used in the present invention includes, but is not limited to: (1) saturated hydrocarbon compounds, such as hexane; (2) aromatic hydrocarbon compounds, such as toluene; (3) glycol ether compounds, such as cellosolve, diethylene glycol diethyl ether, butyl carbitol; (4) glycol ether acetates, such as diethylene glycol butyl ether acetate, carbitol butyl ether acetate; (5) alcohol compounds, such as diacetone alcohol, terpineol, benzyl alcohol; (6) ketone compounds, such as cyclohexanone, methyl ethyl ketone; (7) ester compounds, such as DBE, 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, 2,2,4-trimethyl-1,3-pentanediol diisobutyl ester.
[0050] As a preferred embodiment of the conductive silver paste of the present invention, the mass of the solvent is ≤ 60% of the total mass of the resin, the curing agent, the solvent and the additives.
[0051] The conductive silver paste of the present invention may also contain any auxiliary agent known to those skilled in the art, such as but not limited to: toughening agent, plasticizer, leveling agent, dispersant, diluent, thickener.
[0052] The testing methods of the technical characteristic points of the conductive silver paste prepared in the following embodiments and comparative examples of the present invention are as follows:
[0053] (1) Content of silver powder in the slurry: Weigh a certain amount of slurry, use acetone and toluene solvents to elute it multiple times, dry and weigh the obtained solid, and compare the weight before and after elution;
[0054] (2) Proportion of each component in the silver powder and its average particle size: Weigh a certain amount of slurry, use acetone and toluene solvents to elute and dry it multiple times, resample the obtained solid and take a SEM photo to calculate the proportion of each component in the silver powder and its particle size;
[0055] (3) Type, content, weight-average molecular weight and epoxy equivalent of organic components: Weigh a certain amount of slurry, elute it multiple times with solvents such as acetone and toluene, and dry it. Separate the obtained organic components by thin layer chromatography or column chromatography, and analyze them by infrared spectroscopy and gas chromatography-mass spectrometry to analyze the type, content, weight-average molecular weight and epoxy equivalent characteristics of the organic components.
[0056] Examples 1 to 33 and Comparative Examples 1 to 5
[0057] Examples 1 to 33 and Comparative Examples 1 to 5 are conductive silver pastes of the present invention.
[0058] The mass percentage of the entire silver powder, the type of each organic component and its mass percentage in Examples 1 to 5, Examples 30 to 33 and Comparative Examples 1 to 5 are shown in Tables 1 and 2. The unit of the mass percentage of each component in Table 1 is %. The mass percentage of the entire silver powder, the type of each organic component and its mass percentage in Examples 6 to 29 are the same as those in Example 1.
[0059] The preparation method of the conductive silver paste of Examples 1 to 33 of the present invention and Comparative Examples 1 to 5 comprises the following steps:
[0060] S1. At room temperature, premix all organic components in proportion and perform ultrasonic treatment for 30 minutes under stirring to achieve uniform mixing; for soluble curing agent, the final form is that there is no solid powder in the organic component; for insoluble curing agent, it should be thoroughly ground with the organic component in an agate mortar to achieve uniform dispersion;
[0061] S2. Add silver powder to the mixed material A in step S1, first stir and premix at a speed of 500 r / min, and then disperse evenly through a three-roll mill to obtain the conductive silver paste.
[0062] Table 1
[0063]
[0064] Table 2
[0065]
[0066]
[0067] The weight average molecular weight and epoxy equivalent of the epoxy resin and phenoxy resin in the conductive silver paste of Examples 1, Examples 5-18, and Examples 30-33 are shown in Table 3 below, where the unit of epoxy equivalent is g / eq. The weight average molecular weight and epoxy equivalent of the epoxy resin and phenoxy resin in the conductive silver paste of Examples 2-4, Examples 19-29, and Comparative Examples 1-5 are the same as those in Example 1.
[0068] Table 3
[0069]
[0070]
[0071] In the conductive silver pastes of Example 1, Examples 19 to 29 and Comparative Examples 4 to 5, the mass percentage, particle size, thickness and aspect ratio of the flaky silver powder, spherical silver powder A and spherical silver powder B are shown in Table 4 below, where the mass percentages of the flaky silver powder, spherical silver powder A and spherical silver powder B are all based on the total mass of the conductive silver paste. In the conductive silver pastes of Examples 2 to 18, Examples 30 to 33 and Comparative Examples 1 to 3, the mass percentage, particle size, thickness and aspect ratio of the flaky silver powder, spherical silver powder A and spherical silver powder B are the same as those in Example 1.
[0072] Table 4
[0073]
[0074] Effect example
[0075] The conductive silver pastes of Examples 1 to 33 of the present invention and Comparative Examples 1 to 5 were subjected to performance tests. The test method is as follows:
[0076] (1) Volume resistivity
[0077] Test method: The conductive silver paste is printed onto the ceramic substrate by screen printing, and then placed at 160-200°C (180°C in the present invention) for medium temperature curing for 5-15min (10min in the present invention); Figure 1 The pattern morphology and the grid line height (the grid line height can be measured by various testing methods such as a thick film meter) are used to calculate the volume resistivity of the conductive silver paste according to the definition of volume resistivity.
[0078] Qualification index: Volume resistivity less than 20μΩ·cm is considered qualified.
[0079] (2) Welding tension
[0080] Test method: Use screen printing to Figure 1 The conductive silver paste is printed on a silicon wafer (solar panel) having a reflective layer in the pattern, and is placed at 160-200° C. (180° C. in the present invention) for medium temperature curing for 5-15 minutes (10 minutes in the present invention), according to the following Figure 2 The method described above is used to perform wire welding; on the premise of ensuring that there is no cold welding or over-welding, the welding tension of the gate wire is tested using a handheld tensile gauge; 5 wires are tested for each conductive silver paste, and the average value is taken as the final performance.
[0081] Qualified index: The welding tensile force is considered qualified when it is greater than 2N.
[0082] (3) Shrinkage
[0083] Test method: Use screen printing to Figure 1 The pattern shown is printed on a silicon wafer (solar cell panel) with a reflective layer, and is placed at a medium temperature of 160 to 200° C. (180° C. in the present invention) for curing for 5 to 15 minutes (10 minutes in the present invention), and the pattern thickness before curing (recorded as d1) and the pattern thickness after curing (recorded as d2) are measured, and the shrinkage rate is calculated according to the following formula.
[0084] Qualified index: The shrinkage rate between 18% and 26% is considered qualified.
[0085] Calculation formula:
[0086] (4) Thixotropy test
[0087] Test method: Use a rotational rheometer to test the viscosity of the slurry at a rotation speed of 1 rpm (recorded as N1) and a rotation speed of 5 rpm (recorded as N2), thixotropy = N1 / N2.
[0088] Qualified index: Thixotropy of 2 to 5 is considered qualified.
[0089] The test results are shown in Table 5 below.
[0090] Table 5
[0091]
[0092]
[0093]
[0094] As can be seen from Table 5, by compounding the glycidyl ether epoxy resin and the phenolic epoxy resin and adding a specific phenoxy resin, the conductive silver paste prepared in Examples 1 to 33 not only has a lower volume resistivity, but also has greater thixotropy and welding tension.
[0095] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the conductive silver paste prepared by Comparative Examples 1 to 2, which have a small amount of phenoxy resin added or even do not contain phenoxy resin, has good conductivity. However, since the stress release and crack termination effects cannot be achieved, the welding tension of the conductive silver paste after curing is low, the stability is poor, and it is not conducive to long-term use; while the amount of phenoxy resin used is large, and the viscosity of the conductive silver paste prepared in Comparative Example 3 is large, which seriously damages the integrity of the grid line after the paste is printed, is not conducive to the migration of photoelectrons, thereby increasing the volume resistivity of the conductive silver paste and reducing the conductive performance.
[0096] By comparing Example 1 with Comparative Examples 4 to 5, it can be seen that the ratio of the raw materials in the conductive silver paste is not within the protection scope of the present invention, and the effects of stress release and crack termination cannot be better achieved, resulting in poor thixotropy and welding tension of the conductive silver pastes of Comparative Examples 4 to 5. In addition, the conductive silver paste of Comparative Example 4 has a lower conductivity due to the small amount of silver powder used.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A conductive silver paste, characterized in that: The preparation material comprises the following mass percentages: silver powder 80-94%, epoxy resin 3-6%, curing agent 0.1-10%, solvent 1-5%, additive 1-3%; The epoxy resin includes glycidyl ether epoxy resin and phenolic epoxy resin; Additives include phenoxy resins; The masses of the phenoxy resin, the glycidyl ether epoxy resin and the novolac epoxy resin satisfy the following: S: (a×1.5%+b×6%)=(1-2), wherein: S is the mass of the phenoxy resin, a is the mass of the glycidyl ether epoxy resin, and b is the mass of the novolac epoxy resin; The silver powder includes flaky silver powder, spherical silver powder A and spherical silver powder B; the thickness of the flaky silver powder is 0.5-5 μm, the particle size of the flaky silver powder is 6-15 μm, and the aspect ratio of the flaky silver powder is 2-20; the particle size of the spherical silver powder A is 1-5 μm, and the particle size of the spherical silver powder B is 0.1-3 μm; based on the total mass of the conductive silver paste, the mass percentage of the flaky silver powder is 30-60%, the mass percentage of the spherical silver powder A is 10-30%, and the mass percentage of the spherical silver powder B is 10-30%; The weight average molecular weight ratio of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin is glycidyl ether epoxy resin: novolac epoxy resin: phenoxy resin = 1: (1.5-10): (10-100); The weight average molecular weight of the glycidyl ether epoxy resin is 100-500, the weight average molecular weight of the novolac epoxy resin is 150-5000, and the weight average molecular weight of the phenoxy resin is 10000-80000; The epoxy equivalent ratio of the glycidyl ether epoxy resin, the novolac epoxy resin and the phenoxy resin is glycidyl ether epoxy resin: novolac epoxy resin: phenoxy resin = 1: (1.5-5): (1-10); The epoxy equivalent of the glycidyl ether epoxy resin is 50 to 300 g / eq, the epoxy equivalent of the novolac epoxy resin is 100 to 500 g / eq, and the epoxy equivalent of the phenoxy resin is 500 to 5000 g / eq; In the epoxy resin, the mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin is glycidyl ether epoxy resin:phenolic epoxy resin=(1-4):
1.
2. The conductive silver paste according to claim 1, characterized in that: In the epoxy resin, the mass ratio of the glycidyl ether epoxy resin to the phenolic epoxy resin is glycidyl ether epoxy resin:phenolic epoxy resin=(1.5-3):
1.
3. The conductive silver paste according to claim 1 or 2, characterized in that: The glycidyl ether epoxy resin is selected from bisphenol A epoxy resin and / or bisphenol F epoxy resin, and the novolac epoxy resin is selected from at least one of phenol novolac epoxy resin, cresol novolac epoxy resin and bisphenol A novolac epoxy resin.
4. The conductive silver paste according to claim 1, characterized in that: Based on the total mass of the conductive silver paste, the mass percentage of the flaky silver powder is 45-50%, the mass percentage of the spherical silver powder A is 20-25%, and the mass percentage of the spherical silver powder B is 20-25%.
5. The method for preparing a conductive silver paste according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing epoxy resin, curing agent, solvent and additives in proportion to obtain a mixture A; S2, adding silver powder to the mixed material A in step S1, mixing evenly, to obtain the conductive silver paste.
6. Use of the conductive silver paste according to any one of claims 1 to 4 in the preparation of heterojunction batteries.
Citation Information
Patent Citations
Resin composition containing conducting particle
CN108441156A
Laser etching type conductive silver paste and preparation method and application thereof
CN110853795A